Respuesta :

2(x - 3) + 9 = 3(x + 1) + x


First distribute 2 to both x and -3, and 3 to both x and 1


2(x) = 2x

2(-3) = -6


3(x) = 3x

3(1) = 3


2x - 6 + 9 = 3x + 3 + x


Simplify


2x + 3 = 4x + 3


Isolate the x. Note the equal sign. What you do to one side, you do to the other. Subtract 4x from both sides, and 3 from both sides


2x (-4x) + 3 (-3) = 4x (-4x) + 3 (-3)


2x - 4x = 3 - 3


-2x = 0


Isolate the x, divide -2 from both sides


-2x/-2 = 0/-2


x = 0/-2


x = 0


0 is your answer for x



hope this helps

Answer:

C.x=0

Step-by-step explanation:

x=0 in this equation

ACCESS MORE